KONSEP PENDIDIKAN KH. MUHAMMAD YUSUF HASYIM DAN KONTRIBUSI PEMIKIRANNYA TERHADAP PENDIDIKAN - Sofi Nur, Ahmad; Hosna, Rofiatul; Kholik, Abd. (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This research aims to determine Muhammad Yusuf Hasyim's concept of education and the contribution of his thoughts to education. The expected educational goal is achieved after an effort or activity that proceeds through stages and levels, the goal is gradual and multilevel. The goal of education is not something that is fixed and static. But it is the whole of a person's personality, relating to all aspects of life. Therefore, the concept of KH Perspective education. Yusuf Hasyim refers more to religion, because he prioritizes divinity in education, and also discipline which aims to make education produce success for students, then persistence in education becomes the main driver in the ongoing educational process.